1982
DOI: 10.1113/jphysiol.1982.sp014404
|View full text |Cite
|
Sign up to set email alerts
|

Different types of tremor in the human thumb.

Abstract: 1. The upper limbs of normal subjects were immobilized in a way that allowed measurement of forces and movements at the thumb interphalangeal joint without significant movement elsewhere in the limb. 2. When the subject attempted to maintain a steady flexing force at the joint against a rigid stop, the actual force showed the irregular 8‐11 Hz fluctuations characteristic of a ‘physiological tremor'. This force fluctuation increased when the mean flexing force increased. 3. If the subject exerted his flexing fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 19 publications
(20 reference statements)
3
25
0
Order By: Relevance
“…However, when the frequency of the mechanical component of physiological tremor is reduced by increasing the mass loading of the limb (Joyce and Rack 1974;Brown et al 1982a), a component at 8 -12 Hz remains constant or even shifts to slightly higher frequencies (Elble and Randall 1976;Elble and Randall 1978), suggesting that it has a neural origin. There is a tendency for unfused or partially fused motor unit twitches to cause tremor and while the mean motor unit firing frequency is somewhat higher than the frequency of physiological tremor, there is a tendency for short-term clustering of firing in the range of 8 -12 Hz (Elble and Randall 1976;Elble and Koller 1990; see also Halliday et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the frequency of the mechanical component of physiological tremor is reduced by increasing the mass loading of the limb (Joyce and Rack 1974;Brown et al 1982a), a component at 8 -12 Hz remains constant or even shifts to slightly higher frequencies (Elble and Randall 1976;Elble and Randall 1978), suggesting that it has a neural origin. There is a tendency for unfused or partially fused motor unit twitches to cause tremor and while the mean motor unit firing frequency is somewhat higher than the frequency of physiological tremor, there is a tendency for short-term clustering of firing in the range of 8 -12 Hz (Elble and Randall 1976;Elble and Koller 1990; see also Halliday et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A number of sources of physiological tremor have been suggested, including mechanical resonance of the limb (Joyce and Rack 1974;Elble andRandall 1976, 1978;Brown et al 1982a;Burne et al 1984), synchronisation of motor unit firing (Elble and Randall 1976;Allum et al 1978;Marsden 1984;Elble and Koller 1990;Matthews 1997;Timmer et al 1998a,b; see also Halliday et al 1999) and instability within the stretch reflex arc (Lippold 1970(Lippold , 1971Young and Hagbarth 1980;Zahalak and Cannon 1983;Burne et al 1984;Young 1984, Graham andRedman 1993;Miao and Sakamoto 1997;Sakamoto et al 1998;Santillan et al 2003). The multifactorial nature of tremor was emphasised by Llinas who described it as an "emerging property of various components" (Llinas 1984, p.178).…”
Section: Introductionmentioning
confidence: 99%
“…Also, modelling and experimental studies have shown that the frequency of oscillation of the instability is linked to whether the short (spinal) or long (transcortical) latency pathway of the stretch reflex is predominantly activated [Brown et al, 1982;De Serres et al, 2002;Durbaba et al 2005Durbaba et al , 2013Lippold, 1970;Matthews and Muir, 1980;Stein and Oguztöreli, 1976].…”
Section: Introductionmentioning
confidence: 99%
“…Isometric muscle contraction is accompanied by FT (Allum et al, 1978;Brown et al, 1982). The FT has a broad frequency bandwidth of between 1 and 25 Hz (Allum et al, 1978) and the majority of the FT's frequency bandwidth is in the 3-6 Hz bandwidth related to reflex activity, while the 8-12 Hz bandwidth is related to physiological tremor (Brown et al, 1982;Prochazka and Trend, 1988). Since the main frequency content of the MMG is below 100 Hz (Oster and Jaffe, 1980), it is possible that the frequency spectrums of the FT and the MMG signals overlap.…”
Section: ) Graduate School Of Science and Technology Chiba Universimentioning
confidence: 99%